Time to sputum culture conversion and its predictors among patients with multidrug-resistant tuberculosis in Hangzhou, China: A retrospective cohort study. Issue 50 (11th December 2020) - Li, Qingchun; Lu, Min; Hsieh, Evelyn; Wu, Limin; Wu, Yifei; Wang, Meng; Wang, Le; Zhao, Gang; Xie, Li; Qian, Han-Zhu
Abstract : Abstract: The objective is to investigate the time to initial sputum culture conversion (SCC) and its predictors among multidrug-resistant tuberculosis (MDR-TB) patients in Hangzhou, China. A retrospective cohort study was conducted among patients who initiated MDR-TB treatment from 2011 to 2015 in Hangzhou, China. Successful achievement of initial SCC was defined as 2 consecutive negative cultures taken at least 30 days apart after initiation of treatment of MDR-TB. Successful treatment outcomes included being cured and completing treatment, while poor treatment outcomes included treatment failure, loss to follow-up, and death. Time to initial SCC was analyzed using the Kaplan–Meier method, and Cox proportional hazards regression was used to identify predictors of SCC. Among 384 patients enrolled with MDR-TB, 359 (93.5%) successfully achieved initial SCC after a median of 85 days (interquartile range, 40–112 days). A higher rate of SCC was observed in participants with successful treatment outcomes than those with poor treatment outcomes ( P <.01). Multivariate analysis showed that age 25 to 64 years (compared with age<25; adjusted odds ratio [AOR], 0.7; 95% confidence interval [CI], 0.5–0.9; P < .01), age ≥65 years (compared with age < 25; AOR, 0.5; 95% CI, 0.3–0.8; P < .01), and household registration in Hangzhou (compared with non-Hangzhou registration; AOR, 1.3; 95% CI, 1.0–1.5; P < .05) were found to be associated with SCC. Although high SCC and treatment success rates were observed among MDR-TB patients in Hangzhou, the prolonged duration to initial SCC underscores the importance of emphasizing measures for infection control. A new policy of shifting outpatient treatment to inpatient treatment in China may reduce the risk of transmission from patients in the time window prior to SCC.